Childhood hearing surveillance activity in Italy: preliminary recommendations. - Orzan, E; Ruta, F; Bolzonello, P; Marchi, R; Ceschin, F; Ciciriello, E (Acta Otorhinolaryngol Ital, 2016)
Following the positive outcomes of the newborn hearing screening programmes already underway in several Italian regions, it is now necessary to address the identification of childhood hearing impairments that missed the neonatal screening programme or have delayed onset. Within the framework of the Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for early Identification, Intervention and Care of Hearing Impaired Children", a group of professionals identified three main recommendations that can be useful to improve hearing surveillance activity within the regional and state Italian Health System. The family paediatrician is recognised as having a key role in ongoing monitoring of hearing capacity and development of the growing child.